A three-dimensional network structure of photothermal anti-icing super-hydrophobic coating and preparation method thereof

By preparing a three-dimensional network structure of photothermal anti-icing super-hydrophobic coating, and utilizing the core-shell structure and dynamic imine bond connection of Fe3O4 nanoparticles, the durability problem of super-hydrophobic coating in low temperature and high humidity environment is solved, and efficient anti-icing performance and environmental protection modification are achieved, which is suitable for aerospace, power transmission network, transportation and other fields.

CN119391242BActive Publication Date: 2025-09-23SOUTHWEST JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411656205.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-09-23
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Existing superhydrophobic coatings are susceptible to local vapor penetration and microstructural wear in low-temperature and high-humidity environments, resulting in insufficient mechanical durability, which limits their anti-icing and de-icing applications in aerospace, power transmission grids, and transportation.

Method used

Fe3O4 nanoparticles of different particle sizes were coated with dopamine and then reacted with diamino-terminated polydimethoxysilane to form core-shell structured particles. The particles were connected through dynamic imine bonds and hydrogen bonds to prepare a three-dimensional network structured photothermal anti-icing superhydrophobic coating, and large-area preparation was achieved by spraying.

Benefits of technology

The mechanical durability and photothermal deicing performance of the coating are improved, fluorine-free and environmentally friendly modification is achieved, and the preparation process is simple, making it suitable for large-area applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391242B_ABST
    Figure CN119391242B_ABST
Patent Text Reader

Abstract

The invention discloses a photothermal anti-icing super-hydrophobic coating with a three-dimensional network structure and a preparation method thereof. First, dopamine is reacted with two Fe3O4 particles of different particle sizes to obtain polydopamine-coated Fe3O4 core-shell structure particles, namely n-Fe3O4@PDA and m-Fe3O4@PDA; then, NH2-PDMS-NH2 is used to hydrophobically modify n-Fe3O4@PDA and m-Fe3O4@PDA to obtain Pn-Fe3O4@PDA and Pm-Fe3O4@PDA; secondly, acrylic resin is dissolved in a butyl acetate solution, and then Pn-Fe3O4@PDA and Pm-Fe3O4@PDA, phenylformaldehyde and a small amount of m-Fe3O4@PDA are added to the solution, and the mixture is stirred and mixed to obtain a coating solution; and the coating solution is sprayed on a substrate surface to obtain a super-hydrophobic coating with a three-dimensional network structure. The present invention utilizes dynamic imine bonds to string together partially hydrophobically modified micron core-shell structure particles and completely hydrophobically modified nano core-shell particles, and under the action of hydrogen bonds of a small amount of unmodified micron core-shell particles, a mechanically durable and stable photothermal anti-icing superhydrophobic coating with a three-dimensional network structure is prepared by a simple spraying method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of super-hydrophobic coatings, and in particular to a photothermal anti-icing super-hydrophobic coating with a three-dimensional network structure and a preparation method thereof. Background Art

[0002] Superhydrophobic coatings, due to their high water repellency, are widely used in water treatment, biomedicine, anti-fouling and de-icing, and other fields. However, their fragile micro-nanostructures are easily abraded, limiting their practical application in these fields. Therefore, to realize the anti-icing and de-icing applications of superhydrophobic coatings in aerospace, power grids, and transportation, it is necessary to improve the mechanical durability and stability of superhydrophobic coatings.

[0003] Currently, the mechanical durability of superhydrophobic coatings is primarily addressed by creating rigid armored microstructures on the substrate surface through molding, electrochemical etching, and laser etching to protect the internal nanostructures from damage. These structures, including columnar structures, cavity structures, and interconnected frameworks, can effectively improve the overall mechanical durability of the coating. However, the preparation methods are complex and cannot be prepared on a large scale, limiting their application. Using high-strength metal oxides, carbon-based materials, and ceramic powders as micro-nanostructures, and utilizing high-strength adhesives to enhance the bond between the coating and the substrate, simple spraying methods can form superhydrophobic coatings with self-healing or self-similar structures. This improves the coating's durability to a certain extent, but the excellent durability of the substrate cannot be fully translated into the mechanical durability of the entire coating. Summary of the Invention

[0004] In order to solve the problems of local vapor penetration and microstructure wear of existing super-hydrophobic coatings in low-temperature and high-humidity environments, the present invention provides a three-dimensional network structured photothermal anti-icing super-hydrophobic coating and a preparation method thereof.

[0005] The preparation method of the three-dimensional network structure photothermal anti-icing super-hydrophobic coating provided by the present invention is as follows:

[0006] S1. Add Fe3O4 with a particle size of less than 30 nm to a dopamine (DA) aqueous solution, stir for 30-60 minutes, adjust the solution pH to 8.5, continue stirring for 2-3 hours, centrifuge, and vacuum dry the separated precipitate to obtain black particles of nano-core-shell structure n-Fe3O4@PDA.

[0007] S2. Take Fe3O4 with a particle size of 300-500 nm and prepare m-Fe3O4@PDA with a micron core-shell structure according to the same method as step S1.

[0008] S3. Dissolve the n-Fe3O4@PDA obtained in step S1 in anhydrous ethanol, then add NH2-PDMS-NH2, the weight ratio of n-Fe3O4@PDA to NH2-PDMS-NH2 is (1.2-1.3):2, stir for 20-24 hours, wash with ethanol, and vacuum dry to obtain completely hydrophobically modified nano core-shell structure particles, recorded as Pn-Fe3O4@PDA.

[0009] S4. According to the same method as step S3, the m-Fe3O4@PDA obtained in step S2 is hydrophobically modified. The weight ratio of m-Fe3O4@PDA to NH2-PDMS-NH2 is (1.2-1.3):1 to obtain partially hydrophobically modified micron core-shell structured particles, which are recorded as Pm-Fe3O4@PDA.

[0010] S5. Dissolve acrylic resin (AR) in butyl acetate solution, then add Pn-Fe3O4@PDA prepared in step S3 and Pm-Fe3O4@PDA prepared in step S4, benzaldehyde (BTC) and a small amount of m-Fe3O4@PDA prepared in step S2 to the solution, and stir for 10-20 minutes to obtain a coating solution.

[0011] S6. Spray the coating solution onto the substrate surface to obtain a super-hydrophobic coating with a three-dimensional network structure, which is recorded as AR / NPFe3O4@PDA coating.

[0012] Preferably, in step S1, the weight ratio of Fe3O4 to dopamine is 2:1.

[0013] Preferably, in step S1, the pH of the solution is adjusted to 8.5 using Tris-HCl buffer.

[0014] Preferably, in step S5, the weight ratio of the total weight of Pn-Fe3O4@PDA and Pm-Fe3O4@PDA to the acrylic resin is 3:10. The weight ratio of the amount of m-Fe3O4@PDA to the acrylic resin is 2.5:100. The weight ratio of the amount of benzaldehyde to the acrylic resin is 1.5:100.

[0015] Further preferably, the weight ratio of Pn-Fe3O4@PDA to Pm-Fe3O4@PDA is (0.5-3):1.

[0016] Compared with the prior art, the present invention is beneficial in that:

[0017] (1) The present invention utilizes dynamic imine bonds to string together partially hydrophobically modified micron core-shell structure particles with completely hydrophobically modified nano core-shell particles. Under the action of hydrogen bonds of a small amount of unmodified micron core-shell particles, a three-dimensional network-shaped, mechanically durable and stable photothermal anti-icing super-hydrophobic coating is prepared by a simple spraying method. Among them, n-Fe3O4@PDA and m-Fe3O4@PDA obtained after PDA coating of ferroferric oxide of different particle sizes undergo Schiff base reaction with PDMS (NH2-PDMS-NH2) with double amino end capping, and long-chain double amino end capping polydimethoxysilane is grafted onto the surface of ferroferric oxide to form hydrophobic core-shell nanoparticles Pn-Fe3O4@PDA and Pm-Fe3O4@PDA of different sizes. Long-chain NH2-PDMS-NH2 forms a dynamic imine bond with BTC, which enables Pn-Fe3O4@PDA and Pm-Fe3O4@PDA of different particle sizes to be strung together; a small amount of m-Fe3O4@PDA is added, and the polar groups on the surface of m-Fe3O4@PDA are used to connect the Pm-Fe3O4@PDA particles and between the particles and the matrix through hydrogen bonding, thereby enhancing the bonding strength between the particles and the matrix and further promoting the formation of a three-dimensional cross-linked network structure.

[0018] (2) The core-shell structure formed by PDA coating of rigid micro-nanoferric oxide has high reactivity and photothermal effect, which increases the grafting rate of NH2-PDMS-NH2, thereby improving the photothermal deicing effect of the coating. The resulting micro-nanostructured surface reduces ice adhesion strength. Moreover, the use of NH2-PDMS-NH2 for hydrophobic modification of the coating not only forms a cross-linked network coating, but also achieves fluorine-free modification, making the coating green and environmentally friendly.

[0019] (3) In the present invention, two kinds of ferroferric oxide with different particle sizes are selected. Nano-sized ferroferric oxide plays a super-hydrophobic role, while the introduction of micron-sized ferroferric oxide provides a micron-sized structure to protect the nanostructure from wear, thereby improving the wear resistance of the coating.

[0020] (4) By adjusting the addition ratio of micro-nanoparticles, the self-discharge of condensed droplets and the freezing of water droplets from the outside to the inside can be achieved, thereby improving the photothermal anti-icing performance of the coating.

[0021] (5) The coating preparation process of the present invention is simple, and a three-dimensional cross-linked network structure can be obtained by simple mixing; and a large-area deicing super-hydrophobic coating can be prepared by a simple spraying method.

[0022] Other advantages, objectives and features of the present invention will be reflected in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a diagram of the modification reaction mechanism of Fe3O4 of the present invention.

[0024] Figure 2 Figure 3 is the effect of different n / m ratios on the wear resistance of the coating, where (a) is a coating with n / m=3 and (b) is a coating with n / m=5.

[0025] Figure 3 Comparison of the surface morphologies of the coatings with and without m-Fe3O4@PDA, where (a) is the coating with m-Fe3O4@PDA and (b) is the coating without m-Fe3O4@PDA.

[0026] Figure 4 The changes in morphology and contact angle of the network coating AR / NPFe3O4@PDA and the mixed coating AR / HPFe3O4@PDA before and after wear, where (a) is the network coating AR / NPFe3O4@PDA and (b) is the mixed coating AR / HPFe3O4@PDA. DETAILED DESCRIPTION

[0027] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0028] Example 1

[0029] A method for preparing a three-dimensional network structured photothermal anti-icing super-hydrophobic coating is as follows:

[0030] S1. Weigh 0.5 g of DA and dissolve it in 500 ml of deionized water. Then add 1 g of ferrosoferric oxide (particle size 20 nm). After stirring at room temperature for 30-60 min, adjust the solution pH to 8.5 with Tris-HCl buffer. Continue stirring for 2-3 h, centrifuge at 8000 rpm for 3-5 min, and then dry in a vacuum drying oven at 50°C for 1 h to obtain black particles of n-Fe3O4@PDA.

[0031] S2. Weigh 0.5 g of DA and dissolve it in 500 ml of deionized water. Then add 1 g of ferrosoferric oxide (particle size 300-500 nm). After stirring at room temperature for 30-60 min, adjust the solution pH to 8.5 with Tris-HCl buffer. Continue stirring for 2-3 h, centrifuge at 8000 rpm for 3-5 min, and then dry in a vacuum drying oven at 50°C for 1 h to obtain black particles m-Fe3O4@PDA.

[0032] S3. Dissolve 1.2 g of n-Fe3O4@PDA obtained in step S1 in 60 ml of anhydrous ethanol solution, then add 0.2 g of NH2-PDMS-NH2 and stir at room temperature for 24 h. Wash three times with ethanol solution and then dry in a vacuum drying oven to obtain hydrophobically modified core-shell structure particles, recorded as Pn-Fe3O4@PDA.

[0033] S4, 1.2g of m-Fe3O4@PDA obtained in step S2 was dissolved in 60ml of anhydrous ethanol solution, and then 0.1g of NH2-PDMS-NH2 was added and stirred at room temperature for 24h. After washing three times with ethanol solution, the mixture was vacuum dried in a vacuum drying oven to obtain hydrophobically modified core-shell structure particles, which were recorded as Pm-Fe3O4@PDA. The chemical reaction process involved in steps S1-S4 is as follows: Figure 1 shown.

[0034] S5. Dissolve 0.2 g of AR in 10 ml of butyl acetate solution and stir until the solution is transparent. Then weigh 0.06 g of the total weight of Pn-Fe3O4@PDA and Pm-Fe3O4@PDA. Then, weigh 0.003 g of BTC and 0.005 g of m-Fe3O4@PDA and add them to the solution. Stir for 10-20 minutes to obtain a coating solution. The ratio of Pn-Fe3O4@PDA to Pm-Fe3O4@PDA can be adjusted.

[0035] S6. Add the coating solution into a spray gun with a diameter of 0.5 mm and spray it evenly on the surface of the Q235 substrate under a pressure of 0.5 MPa to obtain a super-hydrophobic coating with a three-dimensional network structure, which is recorded as AR / NPFe3O4@PDA.

[0036] The Q235 surface needs to be pretreated before spraying: the Q235 surface is polished with sandpaper, then ultrasonically cleaned in acetone solution and ethanol solution, blown dry after washing with water, and then sandblasted with quartz sand.

[0037] The performance of super hydrophobic coating is studied as follows:

[0038] (1) In step S5, the effect of the weight ratio of Pn-Fe3O4@PDA and Pm-Fe3O4@PDA on the coating performance was studied while maintaining the total weight of Pn-Fe3O4@PDA and Pm-Fe3O4@PDA at 0.06 g. The results showed that when the weight ratio of Pn-Fe3O4@PDA and Pm-Fe3O4@PDA was 1.3 (n / m=1.3), the wear resistance of the coating was the best. As the n / m ratio continued to increase, the reduction of the microstructure led to a decrease in the wear resistance of the coating. Figure 2As shown, (a) is a coating with n / m=3, and (b) is a coating with n / m=5. As the n / m ratio increases to 5, cracks appear in the coating after 400 friction cycles.

[0039] (2) The surface morphology of the coating prepared in Example 1 is as follows Figure 3 (a) As shown in Example 1, in step S5, without adding m-Fe3O4@PDA, the surface morphology of the coating obtained is as follows Figure 3 As shown in Figure 2 (b), the coating with m-Fe3O4@PDA exhibits a more pronounced cross-linked network structure, while the absence of m-Fe3O4@PDA reduces the degree of cross-linking. This is because the addition of a small amount of m-Fe3O4@PDA allows the polar groups on the surface of m-Fe3O4@PDA to connect the Pm-Fe3O4@PDA particles with each other and with the matrix, promoting the formation of a cross-linked network and enhancing the bonding strength between the particles and the matrix.

[0040] (3) According to the preparation method of Example 1, n / m=3 was controlled, and the resulting mesh coating was AR / NPFe3O4@PDA. In order to compare with conventional mixed coatings, the hydrophobically modified Pn-Fe3O4@PDA and Pm-Fe3O4@PDA were directly added to the ethyl acetate solution of AR at a ratio of n / m=3, without adding BTC and m-Fe3O4@PDA, and sprayed to obtain the coating AR / HPFe3O4@PDA. The specific preparation method is as follows: 0.2g of AR was dissolved in 10ml of butyl acetate solution, stirred until the solution was transparent, 0.06g of Pn-Fe3O4@PDA and Pm-Fe3O4@PDA were weighed at a ratio of n / m=3, stirred for 20 minutes, and then added to a 0.5mm caliber spray gun. The mixture was evenly sprayed on the substrate surface at a pressure of 0.5MPa to obtain the mixed coating AR / HPFe3O4@PDA.

[0041] Figure 4(a) shows the changes in morphology and contact angle of the network coating AR / NPFe3O4@PDA before and after abrasion, while (b) shows the changes in morphology and contact angle of the hybrid coating AR / HPFe3O4@PDA before and after abrasion. It can be seen that a fibrous cross-linked network encapsulating a large number of micro-nanoparticles forms on the surface of the AR / NPFe3O4@PDA coating, resulting in a high contact angle of 162.1°. After 600 abrasion cycles, the contact angle decreases to 150.2°. The PFe3O4 encapsulated by the AR is released during the abrasion process, thus maintaining the micro-nanostructure of the coating surface. On the AR / HPFe3O4@PDA coating, the contact angle reaches 157.6°. After 600 abrasion cycles, the contact angle decreases to 132.4°, and the surface is flattened. This is because in the AR / NPFe3O4@PDA coating of the present invention, a dynamic structure is formed between the two micro- and nano-sized PFe3O4@PDA and BTC and m-Fe3O4@PDA. The formed local network structure affects the arrangement of AR macromolecular chains, induces the formation of fiber structure, promotes the formation of network structure, and effectively improves the wear resistance of the coating.

[0042] Table 1 shows the surface temperature changes of the network coating AR / NPFe3O4@PDA and the hybrid coating AR / HPFe3O4@PDA as a function of illumination time. It can be seen that the network coating AR / NPFe3O4@PDA has a higher photothermal effect than the hybrid coating AR / HPFe3O4@PDA. At 180 seconds, the surface temperature of AR / NPFe3O4@PDA reached 103°C, while that of AR / HPFe3O4@PDA was 93.9°C. This is because in the AR / NPFe3O4@PDA coating of the present invention, the two micro- and nano-sized PFe3O4@PDA particles are encapsulated in the fiber structure, forming a continuous thermal channel, thereby enhancing the photothermal effect.

[0043] Table 1. Changes in surface temperature of mesh coating AR / NPFe3O4@PDA and mixed coating AR / HPFe3O4@PDA with illumination time

[0044]

[0045] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a three-dimensional network structured photothermal anti-icing super-hydrophobic coating, characterized in that: The following steps are involved: S1. Add Fe3O4 with a particle size of less than 30 nm to a dopamine aqueous solution, stir for 30-60 min, adjust the solution pH to 8.5, continue stirring for 2-3 h, centrifuge, and vacuum dry the separated precipitate to obtain n-Fe3O4@PDA with a nano-core-shell structure as black particles; S2, take another Fe3O4 with a particle size of 300-500 nm, and prepare m-Fe3O4@PDA with a micron core-shell structure according to the same method as step S1; S3, dissolving the n-Fe3O4@PDA obtained in step S1 in anhydrous ethanol, and then adding NH2-PDMS-NH2, the weight ratio of n-Fe3O4@PDA to NH2-PDMS-NH2 is (1.2-1.3):2, stirring for 20-24 hours, washing with ethanol, and vacuum drying to obtain completely hydrophobically modified nano core-shell structure particles, recorded as Pn-Fe3O4@PDA; S4. According to the same method as step S3, the m-Fe3O4@PDA obtained in step S2 is hydrophobically modified, and the weight ratio of m-Fe3O4@PDA to NH2-PDMS-NH2 is (1.2-1.3):1 to obtain partially hydrophobically modified micron core-shell structure particles, which are recorded as Pm-Fe3O4@PDA; S5. Dissolve the acrylic resin in butyl acetate solution, then add the Pn-Fe3O4@PDA prepared in step S3, the Pm-Fe3O4@PDA prepared in step S4, benzaldehyde, and the m-Fe3O4@PDA prepared in step S2 to the solution, and stir for 10-20 minutes to obtain a coating solution; S6. Spray the coating solution onto the substrate surface to obtain a super-hydrophobic coating with a three-dimensional network structure, which is recorded as AR / NPFe3O4@PDA coating.

2. The method for preparing a photothermal anti-icing super-hydrophobic coating of a three-dimensional network structure according to claim 1, wherein: In step S1, the weight ratio of Fe3O4 to dopamine is 2:

1.

3. The method for preparing the photothermal anti-icing super-hydrophobic coating of the three-dimensional network structure according to claim 1, wherein In step S1, the pH of the solution is adjusted to 8.5 using Tris-HCl buffer.

4. The method for preparing a three-dimensional network structured photothermal anti-icing super-hydrophobic coating according to claim 1, wherein: In step S5, the weight ratio of the total weight of Pn-Fe3O4@PDA and Pm-Fe3O4@PDA to the acrylic resin is 3:

10.

5. The method for preparing the photothermal anti-icing super-hydrophobic coating of the three-dimensional network structure according to claim 4, wherein: In step S5, the weight ratio of Pn-Fe3O4@PDA to Pm-Fe3O4@PDA is (0.5-3):

1.

6. The method for preparing the photothermal anti-icing super-hydrophobic coating of the three-dimensional network structure according to claim 1, wherein: In step S5, the weight ratio of m-Fe3O4@PDA to acrylic resin is 2.5:

100.

7. The method for preparing the photothermal anti-icing super-hydrophobic coating of the three-dimensional network structure according to claim 1, characterized in that: In step S5, the weight ratio of benzaldehyde to acrylic resin is 1.5:

100.

8. A three-dimensional network structured photothermal anti-icing super-hydrophobic coating, characterized in that: The method is as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Aqueous coating material capable of performing super-hydrophobicity repair through photothermal method, and preparation method thereof

    CN105295698A

  • Double-response self-repairing super-hydrophobic coating material and preparation method thereof

    CN111534190A